Fcγ receptor profile of monocytes and macrophages from rheumatoid arthritis patients and their response to immune complexes formed with autoantibodies to citrullinated proteins. Issue 6 (15th March 2011) - Laurent, Lætitia; Clavel, Cyril; Lemaire, Olivia; Anquetil, Florence; Cornillet, Martin; Zabraniecki, Laurent; Nogueira, Leonor; Fournié, Bernard; Serre, Guy; Sebbag, Mireille
Abstract : Objective: To analyse Fcγ receptor (FcγR) expression on monocytes and macrophages from rheumatoid arthritis (RA) patients versus healthy controls (HC), and to compare their responses to immune complexes containing RA-specific anti-citrullinated proteins auto antibodies (ACPA). Methods: Monocytes and monocyte-derived macrophages were obtained from the peripheral blood of 34 RA patients and 69 HC. FcγR expression was studied by flow cytometry. Cells were stimulated with ACPA-containing immune complexes, and tumour necrosis factor alpha (TNFα) was assayed in culture supernatants. Results: Variations distinguished RA from HC monocytes, corresponding to a 5% and 6% decrease in the percentages of monocytes expressing FcγRI and FcγRII, respectively, and a 7% increase in the proportion of FcγRIII-positive monocytes. Although in both HC and RA patients macrophage differentiation was accompanied by a dramatic increase in the percentage of FcγRIII-expressing cells (72% vs 74.5%), the parallel decline in the proportion of FcγRI-positive cells was markedly smaller in RA (7% vs 43%). Monocytes and macrophages from patients were responsive to ACPA-containing immune complexes but TNFα production in both cell types neither differed from that observed with the corresponding cells from HC, nor correlated with FcγR expression or clinical or biological data. In RA as in HC, ACPA-containing immune complexes induced secretions of more TNFα in macrophages than in paired monocytes (ninefold). Finally, the proinflammatory potential of ACPA-containing immune complexes was confirmed in CD14-positive monocyte macrophages from the synovial fluid of four RA patients. Conclusions: ACPA-containing immune complexes induce TNFα secretion by blood and synovial fluid-derived macrophages from RA patients, fitting with their probable involvement in RA pathophysiology.